What are the Key Factors Shaping Purchase Decisions? A Review of Preferred Green Features Among Potential Homebuyers - Azizul, Ardini Firas; CHUWENI, NOR NAZIHAH (Research in Management of Technology and Business, 2024)
Residential properties are crucial for meeting basic human needs, enhancing stability, and improving quality of life. Since the 1960s, there has been a growing interest in investing in environmentally friendly real estate to reduce greenhouse gas emissions and combat global warming. Extensive green property elements have been incorporated globally, with home purchasers' preferences varying based on their culture, lifestyle, and personal preferences. This study aims to create a comprehensive review and provide framework for potential homeowners particularly the factors influencing the decision to purchase green residential properties in Kuala Lumpur. To achieve this, both empirical and conceptual papers were reviewed. A total of 3,525 articles were discovered in several e-databases using the keywords: 'green residential,' 'green real estate,' 'green building,' 'sustainable building,' and ‘homebuyer.' Following the filtration process, 19 full-text papers relevant to the subject were chosen for review. The analysis identified five criteria that drive property buyers or investor-owned individuals to invest in or purchase green residential property namely financial, locations, design, neighbourhood and policies in green buildings could influence customers' decisions to purchase them. Property developers must comprehend the aspects that may impact consumers' purchasing intentions to maintain a competitive edge in the current market. Understanding sustainability aspects is crucial for developers, legislators, and real estate professionals to fulfil the changing demands and tastes of consumers as sustainability becomes increasingly important in the housing market.